2021
DOI: 10.17159/2309-8988/2021/v37a6
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of a Heated Gas-solid Fluidised Bed using Eulerian Based Models

Abstract: An Eulerian-Eulerian granular model was used to simulate the flow and heat transfer through a heatedgassolid fluidised bed. The primary objective of the study was to determine whether the Eulerian-Eulerian granular model adequately predicts the chamber pressure drop, temperature, and bed expansion through the bed. The model predictions were assessed and validated for various flow-regimes, namely the fixed-bed, smooth, bubbling fluidisation, and the maximum fluidisation regimes. This was done on an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…It was reported that increasing carboxy methyl cellulose concentration increased the net drop in pressure through the bed and the liquid holdup, while the gas holdup and bed expansion were found to decrease. Simulation of the heat transfer and flow rate through a turbulent gas-solid fluidized bed using the Eulerian-Eulerian granular flow model was done [11] and it accurately predicted the chamber pressure difference, temperature change, and bed expansion.…”
Section: Shukla Et Almentioning
confidence: 99%
“…It was reported that increasing carboxy methyl cellulose concentration increased the net drop in pressure through the bed and the liquid holdup, while the gas holdup and bed expansion were found to decrease. Simulation of the heat transfer and flow rate through a turbulent gas-solid fluidized bed using the Eulerian-Eulerian granular flow model was done [11] and it accurately predicted the chamber pressure difference, temperature change, and bed expansion.…”
Section: Shukla Et Almentioning
confidence: 99%